KONSEP SYADZ DAN APLIKASINYA DALAM MENENTUKAN KUALITAS HADIS - Aan Supian (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2015)
In various research traditions, rules avoid syadz often overlooked in the application as a rule the validity of hadith.  This is due,  search around conception syadz including  a study of a difficult and  rarely done  by the scholars of hadith.  Therefore understandable if the benchmarks avoid syadz as a rule the validity of hadith  has not been formulated systematically and  methodologically. This article studies will be directed at the problem: How syadz  conception according to hadith  scholars?  How methodological steps  to determine syadz  and  its application in the study of hadith? and How the formulation of rules to avoid minor syadz as the criterion validity of Matan hadith? Based on the results of the study showed that there was no uniformity of views among  scholars about  the  conception syadz. Especially  notable differences occur  between three  famous  hadith  scholars, al- Shafi’i, al-Hakim and Abu Ya’la al-Khaliliy. A conception which is often referred to by the majority of scholars of hadith is the opinion of Imam Shafi’i. According to al-Shafi’i a hadith contains syadz only if the hadith narrated by a narrator  tsiqat, and violate or contradict the hadith narrated by a number of other tsiqat narrator. The steps that can be taken in tracing the traditions  containing syadz, it can simply be done  with inventory to convey traditions and compare them,  as well as examining the quality rawinya